PROFILE OF STUDENTS’ PROBLEM-SOLVING ABILITY BASED ON MATHEMATICAL LITERACY IN PISA CONTEXT - Sarmila, Sarmila; Tahir, Tahir; Hidayati, Ully (Universitas Sembilanbelas November Kolaka, 2025)
Mathematical literacy plays a crucial role in developing students’ ability to solve contextual mathematical problems. This study aims to describe the profiles of students’ problem-solving abilities based on their levels of mathematical literacy in solving PISA-based questions. A descriptive qualitative approach was employed involving 28 eighth-grade students from SMP Negeri 1 Kolaka selected through purposive sampling. The students were grouped into three categories-high, medium, and low-based on their mathematical literacy test scores. The subjects were selected based on teacher recommendations, namely students with good communication skills who represented each mathematical literacy group. Data were collected using problem-solving tests and interviews, and the instruments were validated by mathematics education experts and teachers. Data analysis followed the Miles and Huberman model, including data reduction, presentation, and conclusion drawing, with source triangulation to ensure validity and credibility. The results showed that students with high mathematical literacy demonstrated comprehensive understanding, effective planning, and accurate problem-solving processes, though minor computational errors were found. Students with medium mathematical literacy could understand problems and plan solutions but often made mistakes in calculations and rarely verified their results. Students with low mathematical literacy only reached the problem-understanding stage and struggled with technical computations, leading to incomplete solutions. Overall, the findings indicate a progressive relationship between mathematical literacy and the completeness of problem-solving stages. The study suggests that integrating PISA-oriented contextual problems into mathematics learning can be a consideration for teachers to train students’ problem-solving and reasoning skills.